2003
DOI: 10.1002/food.200390063
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of protein nutritional quality and effects of traditional processes: A comparison between Ethiopian quality protein maize and five Ethiopian adapted normal maize cultivars

Abstract: The present study was designed to quantitatively measure and compare the levels and variations of total protein, individual amino acids, and computed protein efficiency ratio (C-PER) in raw and traditionally processed products of one recently released quality protein maize (QPM BH542) with four high-yield maize hybrids, namely flint BH660, semi-dent BH140, Pioneer 30H83, and Pioneer 30G97, as well as one local maize cultivar. The total protein content was variable among the cultivars ranging from 7% for BH660 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 27 publications
3
17
0
2
Order By: Relevance
“…An average protein is also shown through sampling for QPM maize of 12.56% and for normal maize of 8.172%, this indicates an increase of 34.94% for the QPM genotype. Similar results are reported by CuevasRodríguez et al (2004) who describe in their paper protein Fufa et al (2003) encontraron que la proteína oscila de 7 hasta 11.8% entre híbridos normales y QPMs, respectivamente. Mendoza et al (2006) reportan de un estudio de triptófano un valor de 11% de proteína en maíz QPM, esta ventaja en el porciento de proteína del QPM se atribuye al gen Opaco-2 (Ortega et al, 2001).…”
Section: Cuadro 1 Comparación De Medias Del Rendimiento De Forraje Vsupporting
confidence: 89%
See 3 more Smart Citations
“…An average protein is also shown through sampling for QPM maize of 12.56% and for normal maize of 8.172%, this indicates an increase of 34.94% for the QPM genotype. Similar results are reported by CuevasRodríguez et al (2004) who describe in their paper protein Fufa et al (2003) encontraron que la proteína oscila de 7 hasta 11.8% entre híbridos normales y QPMs, respectivamente. Mendoza et al (2006) reportan de un estudio de triptófano un valor de 11% de proteína en maíz QPM, esta ventaja en el porciento de proteína del QPM se atribuye al gen Opaco-2 (Ortega et al, 2001).…”
Section: Cuadro 1 Comparación De Medias Del Rendimiento De Forraje Vsupporting
confidence: 89%
“…In another similar study, Fufa et al (2003) found that the protein oscillates from 7 to 11.8% among normal hybrids and QPMs, respectively. Mendoza et al (2006) report from a tryptophan study a 11% of protein in QPM maize, this advantage in the percentage of QPM protein is attributed to the gene Opaque-2 (Ortega et al, 2001).…”
Section: Cuadro 1 Comparación De Medias Del Rendimiento De Forraje Vmentioning
confidence: 79%
See 2 more Smart Citations
“…É um alimento essencialmente energético e protéico (Fufa et al, 2003), em cuja composição contém 60% de carboidratos, 10% de proteínas, 4% de lipídios, além de minerais e vitaminas (Fancelli & Lima, 1982).…”
Section: Introductionunclassified